1990
DOI: 10.1002/jpln.19901530512
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of trace metals by suction cups of aluminium oxide, ceramic and plastics

Abstract: The sorption properties of ceramic, aluminium oxide and plastic suction cups in respect to trace metals (Be, Cd, Co, Cu, Mn, Ni, Pb, Zn) were compared in laboratory and field experiments. The sorption effect is determined by the level of the cation exchange capacity of the cup material, the pH‐value of the soil solution, the content of dissolved organic carbon, the sampling rate and the sampled volume. Sorption was generally negligible only in case of cobalt, manganese and nickel. At low pH‐values no retention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
10
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 10 publications
(5 reference statements)
4
10
0
1
Order By: Relevance
“…Adsorption accounted for 75 ?6 of the lead added with no significant difference being between old and new cups. This confirms to the data of Grossmann et al (1990) who found lead to be the only trace metal adsorbed in significant amounts by ceramic suction cups at pH 4.…”
Section: Aluminum Activity Directly Controls Doc Concentrationsupporting
confidence: 92%
“…Adsorption accounted for 75 ?6 of the lead added with no significant difference being between old and new cups. This confirms to the data of Grossmann et al (1990) who found lead to be the only trace metal adsorbed in significant amounts by ceramic suction cups at pH 4.…”
Section: Aluminum Activity Directly Controls Doc Concentrationsupporting
confidence: 92%
“…Wenzel et al (1997) found that a nylon suction cup had no effect on the heavy metal ion concentration in the solution pumped through. Grossmann et al (1990) also found that heavy metal ions did not adsorb to a nylon cup. However, Grossmann et al (1990) used 10 L of test solution to equilibrate the cups beforehand.…”
mentioning
confidence: 95%
“…Grossmann et al (1990) also found that heavy metal ions did not adsorb to a nylon cup. However, Grossmann et al (1990) used 10 L of test solution to equilibrate the cups beforehand. In a test of suction cups made of PTFE, ceramic, steel, and glass McGuire et al (1992) found that PTFE cups were the best choice for sampling heavy metal ions at low concentrations.…”
mentioning
confidence: 95%
“…As a result, the cups will damp out sudden changes in solution chemistry (Hughes and Reynolds 1988). Also, the presence of dissolved organic carbon (DOC) in soil solution has a dual effect on cation sampling efficiencies (Grossmann, Bredemeier, and Udluft 1990). First, DOC is able to form complexes with cations and hence prevents cation exchange with the cup material.…”
Section: Cationsmentioning
confidence: 99%